Technology, the global economy and other new challenges for civil justice / edited by Koichi Miki. - Miki, Kōichi, 1958- (Intersentia, 2021)
This is a fresh and stimulating book on new challenges for civil justice. It brings together leading experts from across the world to discuss relevant topics of civil justice from regional, cross-border, international and comparative perspectives. Inter alia, this book will focus on multinational rules and systems of dispute resolution in the era of a global economy, while also exploring accountability and transparency in the course of civil justice. Transnational cooperation in cross-border insolvency, regionalism in the process of recognition and enforcement of foreign titles, and the application of electronic technologies in judicial proceedings, including new types of evidence also play a major role. Technology, the Global Economy and other New Challenges for Civil Justice is a compact and accessible overview of new developments in the field from across the world and written for those with an interest in civil justice.